Value of demand flexibility for managing wind energy constraint and curtailment. (May 2022) - Agbonaye, Osaru; Keatley, Patrick; Huang, Ye; Odiase, Friday O.; Hewitt, Neil
Abstract: The dispatch-down of excess wind energy is a growing concern, especially for countries integrating high levels of variable renewable energy. Demand flexibility presents an opportunity to move consumers loads to periods of excess wind energy, which could provide numerous values to the system. While previous research has focused on managing wind energy curtailment (a system-wide issue), much wind energy is rejected due to constraint (a local issue) and hence can only be resolved by local load-on-demand. This paper provides a framework to assess the value of demand flexibility for managing wind energy constraint and curtailment. A methodology to determine the optimal number of subscribers to yield sufficient reduction in excess wind energy while ensuring reasonable cost savings for the subscribers is developed. Analysis shows that this optimal number of subscribers could provide a 67% reduction in constraint and a 74% reduction in curtailment. Consumers can save up to £220 per year, depending on their priority in the dispatch process. A 10-MW wind farm could earn £19, 400 annually from avoided curtailments. System operators could save up to 78% on constraint payments. The paper also assesses the network impact of flexible loads and provides a methodology for calculating the heat-pump hosting capacity of the grid. Highlights: A framework for utilizing wasted wind energy for heating homes is investigated. Currently wasted wind energy could save fuel poor households up to £220 per year. A 10 MW wind farm could earn about £20, 000 annually from avoided curtailment. System Operators could save up to 78% on constraint payments. Mathematical model to determine heat pump hosting capacity of a grid is developed.